The Effect of Virgin Coconut Oil (VCO) on Reducing Blood Sugar Levels in Patients with Type 2 Diabetes - Adi Nurapandi; Irpan Ali Rahman; Henri Setiawan; Dimas Irawan (Universitas Malahayati, 2025)
ABSTRACT Diabetes mellitus is a type of non-communicable disease caused by the body's immune system attacking and damaging pancreatic cells that produce insulin. The number of people with Diabetes Mellitus (DM) tends to increase every year. The utilization of non-pharmacological therapy as a treatment option helps reduce the cost of therapy and treatment for people with VCO diabetes mellitus. The purpose of this study was to determine the effect of virgin coconut oil (VCO) on reducing blood glucose levels of patients with Type II DM at the Cisaga Health Center.This type of research is a pre-experiment with a one group pretest-postest design. Respondents were type 2 DM sufferers as many as 34 respondents who were calculated using G-Power Software. The research was conducted in the work area of the Cisaga Health Center, Ciamis Regency. The instrument used was glucometer (GDS) and the data was processed with SPSS.VCO given to respondents after pretest - postest obtained a sig p-value of 0.000 less than 0.05 and the z-Score is (-) 5.008. From the research that has been done, it can be concluded that there is a significant effect between the decrease in blood sugar in patients with Type 2 DM after being given VCO Virgin Coconut Oil. Keywords: Type 2 Diabetes Mellitus, Virgin Coconut Oil (VCO), Blood Sugar at Time